Pengaruh Solvabilitas Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Intervening : (Studi Pada Subsektor Perusahaan Minyak dan Gas Bumi Yang Terdaftar Di Bursa efek Indonesia Periode 2017-2021) - Fatiha Fani Anggraeni. S; Akhmadi Akhmadi (AKUNTANSI 45, 2023)
During the Covid-19 pandemic in 2020, the oil and gas industry experienced decreased demand, decreased prices, and overproduction (although production decreased). Some oil companies themselves have reduced exploration, including stopping new oil drilling projects. When Covid-19 began to subside, the oil and gas industry again faced the next problem, namely post-pandemic. World oil demand is slowly increasing from a very low level and the impact is that the global economy is starting to return to normal. This research was conducted on the Oil and Gas Subsector in companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The data population is 17 companies and the sample used is 8 companies using purposive sampling method. The variables used in this study are the Solvency Ratio, and Firm Value and Profitability Ratio as intervening variables. The test was carried out by conducting a classical assumption test (normality, multicollinearity and heteroscedasticity) and path analysis test using the SPSS 25 application. The results obtained after conducting research are Solvability has no effect on Profitability, Profitability has no effect on Firm Value, Solvability has an effect on firm value and Profitability cannot mediate the influence between Solvability and Firm Value.